La lámpara arco - Blanco, Aurelio (2011)
El autor comenta el paradigmático diseño del estudio italiano.
Keywords: CASTIGLIONI, ACHILLE; CASTIGLIONI, PIER GIACOMO; DISEÑO INDUSTRIAL; ITALIA; LUMINARIAS; DISEÑO INDUSTRIAL; ITALIA; LUMINARIAS